2015
DOI: 10.1364/oe.23.012111
|View full text |Cite
|
Sign up to set email alerts
|

60-GHz optical/wireless MIMO system integrated with optical subcarrier multiplexing and 2x2 wireless communication

Abstract: This paper proposes a 2x2 MIMO OFDM Radio-over-Fiber scheme based on optical subcarrier multiplexing and 60-GHz MIMO wireless transmission. We also schematically investigated the principle of optical subcarrier multiplexing, which is based on a dual-parallel Mach-Zehnder modulator (DP-MZM). In our simulation result, combining two MIMO OFDM signals to drive DP-MZM gives rise to the PAPR augmentation of less than 0.4 dB, which mitigates nonlinear distortion. Moreover, we applied a Levin-Campello bit-loading algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“… Modulation Up-Conversion Data Rate Source Distance Advances Ref. Coherent Incoherent Fiber Free-Space External Electrical DPSK 0.31 Gbit/s DFBLD 85 km 5 m • Optical SCM 40 Optical DPSK 0.156 Gbit/s 2-λ LD 100 km • Midway Optical Phase Conjugation 41 OOK 7.5 Gbit/s CCS-DSB 2-λ LD 50 km 36 m • 2-λ 23 OOK 2.5 Gbit/s CCS-DSB 4-λ TL 50 km 4 m • 4-λ • Optical SCM 42 OFDM 28 Gbit/s EM Laser 25 km • 2-λ • Optical SCM 28 OFDM 61.5 Gbit/s EM Laser 25 km 3 m • MIMO • Optical SCM • Bit-Loading 43 Direct Electrical OOK 0.622 Gbit/s LD 30 km 3 m • Optoelectronic Mixer 44 Optical OOK 5 Gbit/s DM Laser 100 km • 2-λ (External Modulation) 47 BPSK ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Modulation Up-Conversion Data Rate Source Distance Advances Ref. Coherent Incoherent Fiber Free-Space External Electrical DPSK 0.31 Gbit/s DFBLD 85 km 5 m • Optical SCM 40 Optical DPSK 0.156 Gbit/s 2-λ LD 100 km • Midway Optical Phase Conjugation 41 OOK 7.5 Gbit/s CCS-DSB 2-λ LD 50 km 36 m • 2-λ 23 OOK 2.5 Gbit/s CCS-DSB 4-λ TL 50 km 4 m • 4-λ • Optical SCM 42 OFDM 28 Gbit/s EM Laser 25 km • 2-λ • Optical SCM 28 OFDM 61.5 Gbit/s EM Laser 25 km 3 m • MIMO • Optical SCM • Bit-Loading 43 Direct Electrical OOK 0.622 Gbit/s LD 30 km 3 m • Optoelectronic Mixer 44 Optical OOK 5 Gbit/s DM Laser 100 km • 2-λ (External Modulation) 47 BPSK ...…”
Section: Resultsmentioning
confidence: 99%
“…To further enlarge the transmission capacity, Lin et al . employed the 2 × 2 multi-input multi-output (MIMO) and bit-loading technics to demonstrate a 61.5-Gbit/s OFDM data transmission over 25-km SMF and 3-m free-space 43 . Although the externally modulated method can deliver the high-quality dual-mode optical carrier to demonstrate the high-speed MMWoF system, it cannot be regarded as a cost-effective and simple solution as the additional data encoder is inevitably required.…”
Section: Resultsmentioning
confidence: 99%
“…The straightforward solution to transport independent MIMO signals is to use as many optical links as there are MIMO channels, which leads to an increase in deployment costs. Several works have dealt with this challenge by using different multiplexing schemes to transport mmWave MIMO signals over a single optical link, including Wavelength Division Multiplexing (WDM) [17], Polarization Division Multiplexing (PDM) [18] and Optical Subcarriers Multiplexing (OSCM) [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two LOs are implemented to perform frequency translation of OFDM signals. The authors in [19] used OSCM to transport 2x2 MIMO over Single Mode Fiber (SMF) by using Dual-Parallel Mach-Zehnder Modulators (DP-MZM) and two LOs. However, these architectures are limited to transport only 2x2 MIMO signals.…”
Section: Introductionmentioning
confidence: 99%
“…At mmW frequencies, it has been shown that MIMO gain can be achieved in LOS operation [10]. Recently, a few groups have demonstrated 60GHz LOS MIMO with single RAU operation [11][12][13] and CoMP using a two RAU configuration [14]. But the analysis on Distributed MIMO (or CoMP) transmission to exploit spatial diversity and spatial multiplexing at multiple user locations remains to be performed, to understand the performance enhancement in terms of coverage and data rate improvements that may be gained from such systems.…”
mentioning
confidence: 99%